METODOLOGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS AUGMENTED REALITY ERA SOCIETY 5.0 DI PONPES AR-ROYAN PACITAN - Ismail (LPPM STAI Muhammadiyah Probolinggo, 2026)
The transformation of Islamic Religious Education (PAI) learning in the Society 5.0 era demands the integration of digital technology that is not only instrumental, but also aligned with Islamic values ​​and the characteristics of Islamic boarding school-based educational institutions. Previous research on Augmented Reality (AR) generally focuses on science and language learning, while studies that place AR as an Islamic Religious Education (PAI) learning methodology in the context of Islamic boarding schools are still limited. Therefore, this study aims to examine the effectiveness of the Augmented Reality-based PAI learning methodology as an innovative approach that integrates pedagogical aspects, technology, and religious values ​​at the Ar-Royan Islamic Boarding School in Pacitan. This study employed a qualitative approach with a phenomenological design. Data were collected through unstructured interviews, participant observation, and documentation with Islamic boarding school administrators, Islamic Religious Education teachers, students, and instructional media managers. Data were then analyzed through data reduction, data presentation, and conclusion drawing, ensuring data validity through triangulation techniques. The results show that the application of AR significantly improves students' understanding of religious concepts, learning motivation, and active involvement in the PAI learning process. Furthermore, this methodology is capable of creating contextual, collaborative, and reflective learning by integrating cognitive, affective, and psychomotor dimensions in accordance with the Islamic boarding school (pesantren) educational culture. The findings of this study contribute to the development of an immersive technology-based Islamic Education (PAI) learning methodology model relevant to the Society 5.0 paradigm and provide practical implications for the development of Islamic Education (PAI) learning policies and practices in Islamic educational institutions.